Seminal plasma metabolome in relation to semen quality and urinary phthalate metabolites among Chinese adult men. (August 2019) - Wang, Yi-Xin; Wu, Yan; Chen, Heng-Gui; Duan, Peng; Wang, Liang; Shen, He-Qing; Lu, Wen-Qing; Sun, Bin; Wang, Qi; Zhang, Bo; Chavarro, Jorge E.; Zhang, Jie; et al.
Abstract: Background: A growing body of evidence has found links between endocrine disruptor phthalates and male reproductive disorders, but the mechanisms underlying these relationships are poorly known. Seminal plasma metabolomes may mediate associations of phthalate exposure with impaired semen quality. Objective: To identify seminal plasma metabolomes associated with poor semen quality and evaluate their associations with urinary phthalate metabolites among 660 Chinese adult men. Method: The seminal plasma metabolic profiles were acquired using an untargeted approach based on liquid chromatography-high resolution mass spectrometry. We explored the differences in seminal plasma metabolites between participants with poor and good semen quality and evaluated cross-sectional associations between discriminatory metabolic biomarkers and urinary phthalate metabolites. Results: Differences between poor and good semen quality groups were observed in relation to 25 seminal plasma metabolites, mostly related to the metabolism of polyunsaturated fatty acids (PUFA) and acylcarnitine (all p < 0.05). After adjusting for various confounders and multiple tests, metabolites were all significantly associated with one or more individual sperm quality parameters (motility, concentration, total count, and morphology) (all p < 0.05). Among identified metabolic biomarkers, seminal plasma L-palmitoylcarnitine, linoelaidyl carnitine, and oleic acid were inversely associated with urinary mono-(2-ethylhexyl) phthalate (MEHP), and seminal plasma L-acetylcarnitine was inversely associated with the proportion of di-(2-ethylhexyl)-phthalate metabolites (DEHP) excreted as MEHP in urine (%MEHP) (all p < 0.05). Mediation analysis revealed that oleic acid and L-acetylcarnitine mediated significant proportions (6.7% and 17%, respectively) of the positive associations between urinary DEHP metabolites and the percentage of spermatozoa with an abnormal head. Conclusions: Elevated urinary phthalate metabolites may impact semen quality by causing metabolic disorders of seminal plasma PUFAs and acylcarnitine. These pathways warrant further investigation. Graphical abstract: Unlabelled Image Highlights: Seminal metabolomes differed significantly between poor and good sperm groups. The identified metabolomes were mostly related to PUFA and acylcarnitine metabolism. Seminal plasma L-acetylcarnitine was inversely associated with urinary %MEHP. L-palmitoylcarnitine, linoelaidyl carnitine and oleic acid were associated with MEHP. Some metabolomes mediated the association of DEHP metabolites with sperm morphology.